2022
DOI: 10.1186/s12879-022-07072-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ethnic minority status on tuberculosis diagnosis and treatment delays in Hunan Province, China

Abstract: Background Tuberculosis (TB) continues to be a major public health challenge in China. Understanding TB management delays within the context of China’s unique ethnic diversity may be of value in tackling the disease. This study sought to evaluate the impact of ethnic minority status on TB diagnosis and treatment delays. Methods This retrospective cohort study was conducted on patients diagnosed with TB in Hunan Province, China between 2013 and 2018… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…This is in line with previous research which has found ethnic biases in smaller samples 20–22. More broadly, this adds to a growing body of literature indicating that individuals from ethnic minority backgrounds are identified later than their ethnic majority counterparts in conditions as diverse as autism,28 tuberculosis29 and cancer 30. Importantly, however, there were no ethnic differences in children who entered formal education ‘school ready’, thus indicating that the association between ethnicity and SEN is not universal.…”
Section: Discussionsupporting
confidence: 90%
“…This is in line with previous research which has found ethnic biases in smaller samples 20–22. More broadly, this adds to a growing body of literature indicating that individuals from ethnic minority backgrounds are identified later than their ethnic majority counterparts in conditions as diverse as autism,28 tuberculosis29 and cancer 30. Importantly, however, there were no ethnic differences in children who entered formal education ‘school ready’, thus indicating that the association between ethnicity and SEN is not universal.…”
Section: Discussionsupporting
confidence: 90%
“…Our study did not identify significant differences in TB-related outcomes across ethnic groups. However, various studies conducted in other countries have shown that the migrant population and ethnic minorities have a higher prevalence of TB in comparison to the general population [ 49 53 ]. This could be because of interactions between cultural and structural barriers to accessing healthcare [ 3 , 4 , 50 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Among different occupational groups, students had lower duration of patient delay, likely because they have easier access to relevant health education and medical resources, enabling them to seek diagnosis and treatment earlier [ 34 ]. Additionally, the delay in seeking medical attention was lower among the Han ethnic group compared to minority ethnic groups like the Li people, possibly due to cultural differences between different ethnic groups, unequal distribution of medical resources, and varying levels of awareness of TB [ 35 , 36 ].…”
Section: Discussionmentioning
confidence: 99%